Adapting the Scar-in-a-Jar to Skin Fibrosis and Screening Traditional and Contemporary Anti-Fibrotic Therapies - Coentro, João Q.; May, Ulrike; Prince, Stuart; Zwaagstra, John; Ritvos, Olli; Järvinen, Tero A.H.; Zeugolis, Dimitrios I. (Frontiers in Bioengineering and Biotechnology, 2021)
Skin fibrosis still constitutes an unmet clinical need. Although pharmacological strategies are at the forefront of scientific and technological research and innovation, their clinical translation is hindered by the poor predictive capacity of the currently available in vitro fibrosis models. Indeed, customarily utilised in vitro scarring models are conducted in a low extracellular matrix milieu, which constitutes an oxymoron for the in-hand pathophysiology. Herein, we coupled macromolecular crowding (enhances and accelerates extracellular matrix deposition) with transforming growth factor β1 (TGFβ1; induces trans-differentiation of fibroblasts to myofibroblasts) in human dermal fibroblast cultures to develop a skin fibrosis in vitro model and to screen a range of anti-fibrotic families (corticosteroids, inhibitors of histone deacetylases, inhibitors of collagen crosslinking, inhibitors of TGFβ1 and pleiotropic inhibitors of fibrotic activation). Data obtained demonstrated that macromolecular crowding combined with TGFβ1 significantly enhanced collagen deposition and myofibroblast transformation. Among the anti-fibrotic compounds assessed, trichostatin A (inhibitors of histone deacetylases); serelaxin and pirfenidone (pleiotropic inhibitors of fibrotic activation); and soluble TGFβ receptor trap (inhibitor of TGFβ signalling) resulted in the highest decrease of collagen type I deposition (even higher than triamcinolone acetonide, the gold standard in clinical practice). This study further advocates the potential of macromolecular crowding in the development of in vitro pathophysiology models.